Clinical remission of an inoperable malignant insulinoma by the combination treatment with octreotide and everolimus. (11th January 2019) - Akahori, Hiroshi
Abstract: We report a 52‐year‐old woman with inoperable malignant insulinoma with multiple liver metastases. Histological examination of biopsy specimens from the pancreatic and hepatic lesions revealed pancreatic neuroendocrine tumor (pNET), G2. The tumor cells were positive for somatostatin receptor (SSTR) 2, 5, and the mammalian target of rapamycin (mTOR). Monthly intramuscular administration of octreotide LAR and once‐daily oral administration of everolimus combination treatment markedly reduced the sizes of liver metastases, and hypoglycemia was well controlled. Combination treatment with somatostatin analog and mTOR inhibitor may be another effective approach in inoperable metastatic malignant insulinoma. Abstract : Monthly intramuscular administration of octreotide LAR and once‐daily oral administration of everolimus combination treatment markedly reduced the sizes of liver metastases, and hypoglycemia was well controlled. Combination treatment with somatostatin analog and mTOR inhibitor may be another effective approach in inoperable metastatic malignant insulinoma.